Biotechnologies for Plant Mutation Breeding Protocols - Jankowicz-Cieslak, Joanna; Tai, Thomas H.; Kumlehn, Jochen; Till, Bradley J. (Springer Nature, 2017)
Plant Breeding/Biotechnology; Agriculture; Genetic Engineering; Plant Genetics & Genomics